1999
DOI: 10.1152/ajpgi.1999.276.2.g363
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac impairment and nitric oxide synthase activity in the chronic portal vein-stenosed rat

Abstract: Decreased cardiac contractility and β-adrenergic responses have been observed in the chronic portal vein-stenosed (PVS) rat. Because nitric oxide (NO) may be increased in PVS and has been recognized as a negative inotropic agent, we investigated the induction of NO synthase (NOS2) and/or changes in constitutive NOS (NOS3) as factors in the cardiac dysfunction of the PVS rat. Ten to twelve days after portal vein stenosis or sham operation, cardiac function was evaluated in paced left ventricular papillary muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…33 In hearts of 4-week CBDL models, Liu et al recently showed cytokine activation of iNOS and improvement of papillary muscle contractility when the enzyme was inhibited. 34 This result is in contrast with the increase in eNOS without activation of iNOS observed in aortic rings by the same group 35 and others 36 and with the results in the partial portal vein ligation rat heart 37 in which NOS expression and activity and endproducts resulting from NO pathway did not differ from those in sham hearts. An intriguing aspect of the present results is the mechanism of the persistently increased synthesis of NO by eNOS in isolated hearts.…”
Section: Coronary Vasodilationmentioning
confidence: 63%
“…33 In hearts of 4-week CBDL models, Liu et al recently showed cytokine activation of iNOS and improvement of papillary muscle contractility when the enzyme was inhibited. 34 This result is in contrast with the increase in eNOS without activation of iNOS observed in aortic rings by the same group 35 and others 36 and with the results in the partial portal vein ligation rat heart 37 in which NOS expression and activity and endproducts resulting from NO pathway did not differ from those in sham hearts. An intriguing aspect of the present results is the mechanism of the persistently increased synthesis of NO by eNOS in isolated hearts.…”
Section: Coronary Vasodilationmentioning
confidence: 63%
“…Portal hypertension with portosystemic shunting was produced by calibrated constriction of the portal vein as previously described [2,12,24,25]. Briefly, Sprague-Dawley derived rats were anesthetized with ketamine, 100 mg kg -1 ip, the portal vein was isolated, and a silk ligature was placed around it.…”
Section: Portal Vein Stenosismentioning
confidence: 99%
“…Specifically, these parameters were found to be unaltered in PVS rats, whereas membrane L-type Ca# + channels and sarcoplasmic reticulum caffeine-sensitive calcium stores appeared to be dysfunctional [96]. Given the considerations described above, it is interesting to note that Battarbee and colleagues [94] found no evidence of iNOS or even NO activation in their PVS rats. Even serum levels of nitrites\nitrates were unaltered in their PVS rat model.…”
Section: No In Cirrhotic Cardiomyopathymentioning
confidence: 92%
“…Battarbee and colleagues [94] have recently reported their investigations of NO activity in a rat model of prehepatic portal hypertension due to graded stenosis of the portal vein [portal vein stenosis (PVS) rats]. This rat model does not have any intrinsic liver disease, but mimics the human situation of portal vein obstruction with a ' pure ' presinusoidal portal hypertension.…”
Section: No In Cirrhotic Cardiomyopathymentioning
confidence: 99%